The Effect of Company Reputation and Business Strategy on Company Performance of Banking Industry in Indonesia - Lumban Tobing, Tongam; ., . (International Journal of Engineering and Technology, 2018)
The number of offices and assets of go-public banking has increased, but their performance has grown unstable. The condition is allegedly related to the issues of business strategy and company reputation. Hence, this study aims to examine the influence of company reputation and business strategy on banking performance in Indonesia. The research uses quantitative research approach on unit of analysis national banking that has been go-public. So the population in this study is all national banks including government, private, and foreign owned which have been go-public. The process of observation is cross section / one shot, ie in 2017. The primary data is obtained through questionnaire towards 43 go-public banks conducted by a census. Analysis of causality to answer the purpose of research, use Partial Least Square (PLS). The results show that the company's reputation and business strategy significantly affect the performance of banking companies in Indonesia either simultaneously or partially. Partially, business strategy is more dominant in affecting company performance than company reputation.Â Â Â